Contrasted life trajectories: reconstituting the main population exposomes in French Guiana - Nacher, Mathieu; Basurko, Célia; Douine, Maylis; Lambert, Yann; Rousseau, Cyril; Michaud, Celine; Garlantezec, Ronan; Adenis, Antoine; Gomes, Margarete M; Alsibai, Kinan Drak; Sabbah, Nadia; Lambert, Véronique; et al. (Frontiers in Public Health, 2024)
In French Guiana life expectancy is between 2 to 3 years beneath that of France, reflecting differences in mortality rates that are largely sensitive to primary health care, and thus preventable. However, because poverty affect half of the population in French Guiana, global measurements of life expectancy presumably conflate at least 2 distinct situations: persons who have similar life expectancies as in mainland France and persons living in precariousness who have far greater mortality rates than their wealthier counterparts. We thus aimed to synthesize what is known about statistical regularities regarding exposures and sketch typical French Guiana exposomes in relation with health outcomes. We conducted a narrative review on common exposures in French Guiana and made comparisons between French Guiana and mainland France, between rich and poor in French Guiana, and between urban and rural areas within French Guiana. The most striking fact this panorama shows is that being a fetus or a young child in French Guiana is fraught with multiple threats. In French Guiana poverty and poor pregnancy follow up, renouncing to health care, the wide variety of infectious diseases, the very high prevalence of food insecurity, of psychosocial stress, of micronutrient deficiencies, of obesity and metabolic problems, the frequent exposure to lead and mercury in rural areas constitute a stunningly challenging exposome for a new human being to develop into. A substantial part of the population's health is hence affected by its poverty and its sources of nutrition.